2017
DOI: 10.18632/oncotarget.15874
|View full text |Cite
|
Sign up to set email alerts
|

Search for rare protein altering variants influencing susceptibility to multiple myeloma

Abstract: The genetic basis underlying the inherited risk of developing multiple myeloma (MM) is largely unknown. To examine the impact of rare protein altering variants on the risk of developing MM we analyzed high-coverage exome sequencing data on 513 MM cases and 1,569 healthy controls, performing both single variant and gene burden tests. We did not identify any recurrent coding low-frequency alleles (1–5%) with moderate effect that were statistically associated with MM. In a gene burden analysis we did however iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…By referencing germline whole-genome sequencing (WGS) data on 640 MM patients analyzed as part of the CoMMpass Study ( Craig et al., 2013 ), we were able to confirm that the imputation captured >90% of sequence variation (minor allele frequency [MAF] > 0.05) within the linkage disequilibrium (LD) region encompassing rs11372862 (i.e., pairwise r 2 ≥ 0.1) ( Table S1 ). By analyzing the germline exomes of 513 MM case subjects from the UK Medical Research Council (MRC) MyIX and MyXI clinical trials and 1,569 UK control subjects from the UK 1958 Birth Cohort ( Scales et al., 2017 ), we excluded the possibility that the 5q15 association signal is a consequence of LD with a rare disease-causing coding variant ( Table S2 ).
Figure 1 Regional Plots of Association Results of the 5q15 Locus (A and B) The region of association maps to a ∼40 kb haplotype block within ELL2 .
…”
Section: Resultsmentioning
confidence: 99%
“…By referencing germline whole-genome sequencing (WGS) data on 640 MM patients analyzed as part of the CoMMpass Study ( Craig et al., 2013 ), we were able to confirm that the imputation captured >90% of sequence variation (minor allele frequency [MAF] > 0.05) within the linkage disequilibrium (LD) region encompassing rs11372862 (i.e., pairwise r 2 ≥ 0.1) ( Table S1 ). By analyzing the germline exomes of 513 MM case subjects from the UK Medical Research Council (MRC) MyIX and MyXI clinical trials and 1,569 UK control subjects from the UK 1958 Birth Cohort ( Scales et al., 2017 ), we excluded the possibility that the 5q15 association signal is a consequence of LD with a rare disease-causing coding variant ( Table S2 ).
Figure 1 Regional Plots of Association Results of the 5q15 Locus (A and B) The region of association maps to a ∼40 kb haplotype block within ELL2 .
…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that after silencing KIF18A, cell proliferation, cell invasion and migration decreased in minimally invasive HepG2 cells and highly invasive SMMC-7721 cells. For these changes, the relevant literature suggests that the KIF18A gene causes dysregulation of cell mitosis control and promotes cell division [ 15 ]; however, the mechanism remains uncertain. In one of the Przybyl studies, regulation of impaired mitosis in the early stage of the tumour can cause synsa [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scales et al recently reported an MM exome mutation burden test study in 513 United Kingdom northern EA MM cases from two clinical trials (48). While no individual gene reached genomewide significance in this study, the authors nominated KIF18A as a promising MM predisposition candidate.…”
Section: Discussionmentioning
confidence: 99%